(untitled) (European Journal of Pure and Applied Mathematics, 2022)
In most applications, denoising image is fundamental to subsequent image processing operations. In this research, we derivation a new formula of conjugate gradient methods based on the quadratic model. The fact that the search direction created at each iteration of the proposed approach is descending and independent of the line search makes it interesting. The use of Wolfe conditions also determines the global convergence of the suggested approach. To prove the viability of the suggested approach, comparison tests on impulse noise reduction are given.